Creativity Teaching Practices in Fashion and Apparel Programmes: An Experience-Based Perspective in Malaysian TVET - Noorhana Mohammad,; Zanariah Ahmad, (Journal of Technical Education and Training, 2026)
This study examines creativity teaching practices in Fashion and Apparel programmes at Malaysian Community Colleges, focuses on instructional approaches to enhance students’ creativity. This study highlights the role of lecturers’ teaching practices and professional experiences in shaping creative learning environments. A qualitative case study was designed, involved 15 informants, comprises of three subject-matter experts in Fashion Design and 12 lecturers from Community Colleges and Polytechnics under the Ministry of Higher Education. Data were collected through in-depth interviews, classroom observations, and document analysis, and analysed through thematic analysis guided by Sternberg’s Theory of Creativity. The findings suggest six key dimensions of creativity: intellectual, knowledge, thinking style, personality, motivational, and environmental creativity. These practices contribute to the development of students’ creative skills, particularly in idea generation, problem-solving, and design innovation, through structured guidance, experiential learning, and collaborative engagement. However, several challenges were identified, including limited instructional time, resource constraints, and varying levels of student readiness, which affect the implementation of creativity-based teaching approaches. These findings suggest the need of institutional support to sustain creativity-focused pedagogy. The study provides practical implications for TVET education, particularly in enhancing curriculum design, strengthening lecturer professional development, and informing policy initiatives aimed at integrating creativity-based teaching practices into institutional standards.